2011
DOI: 10.1186/scrt90
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling reveals age-dependent differential expression of nuclear factor κB and mitogen-activated protein kinase in adipose and bone marrow-derived human mesenchymal stem cells

Abstract: IntroductionMesenchymal stem cells (MSCs) play a central role in mediating endogenous repair of cell and tissue damage. Biologic aging is a universal process that results in changes at the cellular and molecular levels. In the present study, the role of microRNA (miRNA) in age-induced molecular changes in MSCs derived from adipose tissue (ASCs) and bone marrow (BMSCs) from young and old human donors were investigated by using an unbiased genome-wide approach.MethodsHuman ASCs and BMSCs from young and old donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 47 publications
(64 reference statements)
11
82
0
1
Order By: Relevance
“…There were no discernible age-associated changes in MSC marker profiles and ADSC differentiation potential, which correlated with results of Pandey et al [43].…”
Section: Discussionsupporting
confidence: 90%
“…There were no discernible age-associated changes in MSC marker profiles and ADSC differentiation potential, which correlated with results of Pandey et al [43].…”
Section: Discussionsupporting
confidence: 90%
“…Another potential therapeutic-related approach might involve targeting the increased oxidative stress occurring with aging. Thus, Miller and coworkers 46 examined the capacity of the ileal artery of aged rats to remodel, in vivo, in response to ligation of adjacent arteries. They found that luminal expansion was absent in aged rats, but that expansion was restored by antioxidant treatment.…”
Section: Speculations On Potential Therapeutic Strategies Deriving Frmentioning
confidence: 99%
“…A similar donor age-dependent decline in VEGF levels has been reported in mouse and rat bone marrow MSCs [18,43] and mouse ASCs [26]. A recent study using human bone marrow MSCs and ASCs demonstrated donor age-associated changes in microRNAs, which regulate expression of several genes and cellular function [23,24]. Further studies are needed to identify the essential molecules, including micro-RNAs, that regulate biological age-dependent VEGF-A expression.…”
Section: Discussionmentioning
confidence: 92%
“…The proliferation and differentiation potential of MSCs/ASCs is known to be affected by in vitro aging (passage number in culture) [18][19][20][21] and by in vivo aging (donor age) [18,20,[22][23][24][25]. On the other hand, limited information is currently available regarding the angiogenic potential of aged ASCs [26][27][28].…”
Section: Introductionmentioning
confidence: 99%